OPRM1 and COMT Gene–Gene Interaction Is Associated With Postoperative Pain and Opioid Consumption After Orthopedic Trauma. (March 2017) - Khalil, Heba; Sereika, Susan M.; Dai, Feng; Alexander, Sheila; Conley, Yvette; Gruen, Gary; Meng, Li; Siska, Peter; Tarkin, Ivan; Henker, Richard
Background: mu-opioid receptor ( OPRM1 ) and catechol-O-methyltransferase ( COMT ) contribute to the neurotransmission pathway of pain. COMT affects mu receptor expression and density in the brain. The aim of this study was to explore the OPRM1 and COMT interaction effects on postoperative pain and opioid consumption. Methods: This cross-sectional exploratory study used genotype and clinical data from 153 postoperative patients. Using multiple regression analyses, four single-nucleotide polymorphisms of COMT (rs6269, rs4633, rs4818, and rs4680), their haplotypes, and diplotypes were considered for their interactions with A118G of OPRM1 regarding postoperative pain and opioid consumption. Results: For opioid consumption, significant interactions were found between OPRM1 A118G and COMT rs4680 ( p = .037) and between OPRM1 and COMT rs4633 ( p = .037). Patients having Met158Met of COMT rs4680 and AG/GG of OPRM1 or TT of COMT rs4633 and AG/GG of OPRM1 consumed the largest amount of opioid compared to those having other combinations. For postoperative pain, a significant interaction was found between OPRM1 and the low pain sensitivity (LPS; GCGG) haplotype of COMT ( p = .017). For patients with no copies of the LPS haplotype, AA of OPRM1 A118G was significantly associated with higher pain scores compared to the variant AG/GG. However, the opposite direction was observed for patients with at least one copy of the LPS haplotype. Conclusions: The interaction of OPRM1 with COMT may contribute to variability in postoperative pain and opioid consumption. Additional larger studies are needed to confirm findings.